A Critical Literature Review of Health Inequalities, Cultural Exclusion, and the Case for a Culturally Appropriate Digital Health Promotion App for Black Communities in England - Basiru Gai; Atiya Kamal; Pelham Carter; Angela Tufte-Hewett (Healthcare, 2026)
Background: Black communities in England experience health inequalities rooted in structural racism, socioeconomic deprivation, and systemic exclusion from health systems that fail to address their specific needs. Digital health technologies offer potential for reducing these disparities, yet the existing evidence reveals an absence of culturally appropriate digital interventions designed with and for Black communities in England. Objective: To synthesise evidence on the structural and cultural determinants of health inequality affecting Black people in England and examine the potential of health apps for delivering culturally appropriate health promotion. Methods: This is a purposive, critical narrative literature review, not a systematic review; it does not aim for exhaustive or fully reproducible search coverage but for a structured, purposive synthesis of the evidence base relevant to four thematic domains. Purposive sampling was used to identify literature across the PubMed/MEDLINE, PsycINFO, Google Scholar, and policy databases. Findings were thematically synthesised around four domains: structural determinants of health inequality; cultural diversity and representation within Black communities; digital inclusion and health app access; and theoretical frameworks for culturally appropriate intervention design. Findings: Three intertwined problems underpin the absence of culturally appropriate digital health tools for Black communities: structural exclusion from health systems; methodological shortcomings of aggregating heterogeneous populations under broad ethnic labels such as BAME; and the systematic exclusion of Black people from digital health design processes. We propose a multi-layered theoretical framework combining the Health Belief Model, Beattie’s community development paradigm, and McCurdie’s user-centred design principles to guide the co-design of a culturally appropriate health promotion app. Conclusions: A culturally appropriate health promotion app for Black communities in England appears to be a promising and potentially feasible direction, provided it is developed through authentic community partnership and grounded in theories that account for structural determinants of health; this conclusion is conceptual, and no user research, prototype testing, or feasibility study has yet been undertaken to confirm it. These are identified as necessary next steps rather than results already achieved.